1979
DOI: 10.1007/bf01408387
|View full text |Cite
|
Sign up to set email alerts
|

Three-particle system for nonlocal interactions with continuum bound states

Abstract: The energy spectrum of the model triton is studied for a series of rank-two separable twobody interactions, each of which has a fixed deuteron wave function and a continuum bound state fixed at high energy. In each case the three particle system collapses, having an unphysical deeply bound ground state. With increasing two body repulsion, the collapsed state becomes less bound. If the continuum bound state moves to higher energies, the collapsed state becomes more bound. Our results show that for non-local two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

1980
1980
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…Pantis, Fiedeldey, and Sprung [4] (PFS) had confirmed the above observations of RST earlier. In addition, using a partly nonlocal potential with an artificial strong repulsion at short distances PFS had demonstrated the appearance of a CBS without having a BSC.…”
Section: Introductionsupporting
confidence: 62%
See 1 more Smart Citation
“…Pantis, Fiedeldey, and Sprung [4] (PFS) had confirmed the above observations of RST earlier. In addition, using a partly nonlocal potential with an artificial strong repulsion at short distances PFS had demonstrated the appearance of a CBS without having a BSC.…”
Section: Introductionsupporting
confidence: 62%
“…The phenomenon of BSC is common to all Tabakin-type potentials. The BSC is not only observed in the case of rank-one potentials, it has also been observed in the case of higher rank potentials [4].…”
Section: Introductionmentioning
confidence: 75%
“…Previous work by Sofianos et al [-1] and Pantis et al [2] has shown that separable potentials of rank 1 and rank 2 which support a continuum bound state (or a resonance pole sufficiently close to the real axis) in the two-particle system, produce unphysical deeply bound states in the three-particle system. With increasing two-body repulsion the collapsed state becomes less bound but it does not go down enough in order to become a physically acceptable ground state.…”
Section: Introductionmentioning
confidence: 98%
“…In the presence of a CBS the binding energy of the usual bound state does not necessarily reflect the strength of the potential. Whenever this potential is used in a multiparticle system it produces stronger binding compared to that produced by an "equivalent" local potential which produces the same negative-energy bound state [7].…”
Section: Introductionmentioning
confidence: 99%
“…A class of similar potentials has been identified later. The use of these potentials in (three-nucleon) 3N and four-nucleon bound-state calculations [7] leads to ground states of unusually large binding of several hundred MeV's in addition to a weakly bound excited state. [7,9,10] One …”
Section: Introductionmentioning
confidence: 99%